Tetrahedral zinc in tetrakis(1-methyl-1H-imidazole-κN3)zinc bis(tetrafluoridoborate) - Jan Reedijk; Gerard A. van Albada; Bart Limburg; Ilpo Mutikainen; Urho Turpeinen (Acta Crystallographica Section E, 2012)
In the title compound, [Zn(C4H6N2)4](BF4)2, the ZnII ion is in a slightly distorted tetrahedral coordination geometry, with Zn—N distances in the range 1.980 (2)–1.991 (2) Å. The tetrahedral angles are in the range 104.93 (9)–118.81 (9)°.